2015
DOI: 10.1021/acsmedchemlett.5b00208
|View full text |Cite
|
Sign up to set email alerts
|

Structural Optimization of Indole Derivatives Acting at Colchicine Binding Site as Potential Anticancer Agents

Abstract: A new series of indole analogues based on our earlier lead compound, 2-(1H-indol-5-yl)-4-(3,4,5-trimethoxyphenyl)-1H-imidazo[4,5-c]pyridine (42), was prepared as tubulin inhibitors in an effort to find a molecule with improved cytotoxic potency and metabolic stability. A series of indolyl-imidazopyridines (IIP) were synthesized and exhibited potent tubulin polymerization inhibitory activity with potent IC 50 values ranging from 3 to 175 nM against a panel of human melanoma and prostate cancer cell lines. Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 24 publications
1
50
0
Order By: Relevance
“…Jianhong et al reported the ability of millepachine to evade MDR in an A2780CP (P‐gp overexpressing) model and demonstrated that it irreversibly interacted with the colchicine site of β tubulin and retained full activity toward MDR cells. DJ101 targeted the colchicine binding site, which was confirmed through X‐ray crystallography, potently reduced cell viability in MDR cell lines, and also significantly inhibited tumor growth in taxane‐resistant prostate cancer xenografts without causing toxicity to the mice . SSE15206 also circumvented drug resistance in KB‐V1 and A2780‐Pac‐Res cell lines that overexpressed P‐gp .…”
Section: Mechanisms Of Multidrug Resistancementioning
confidence: 83%
See 3 more Smart Citations
“…Jianhong et al reported the ability of millepachine to evade MDR in an A2780CP (P‐gp overexpressing) model and demonstrated that it irreversibly interacted with the colchicine site of β tubulin and retained full activity toward MDR cells. DJ101 targeted the colchicine binding site, which was confirmed through X‐ray crystallography, potently reduced cell viability in MDR cell lines, and also significantly inhibited tumor growth in taxane‐resistant prostate cancer xenografts without causing toxicity to the mice . SSE15206 also circumvented drug resistance in KB‐V1 and A2780‐Pac‐Res cell lines that overexpressed P‐gp .…”
Section: Mechanisms Of Multidrug Resistancementioning
confidence: 83%
“…There have been tremendous efforts in developing numerous natural and synthetic small molecules capable of binding to and affecting MT dynamics . However, these MT‐targeting agents offer broad diversity in terms of their chemical structures and tubulin protein binding sites, suggesting a potential affinity to bind to proteins other than tubulin .…”
Section: Tubulin Kinase Dual Inhibition In Anticancer Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…2‐phenylindole derivatives are attractive anti‐breast cancer agents as shown in Figure ,. These derivatives can overcome multi‐drug resistance in cancer by interacting into the colchicine binding site on tubulin . Due to such enormous medicinal applications, the synthesis of various indole derivatives, particularly 2‐phenylindole derivatives using newer and efficient methodology is of immense interest in recent years .…”
Section: Figurementioning
confidence: 99%